2019
DOI: 10.1177/1082013219883054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical effect of ultrasound on sweet potato starch and its influence mechanism on the quality of octenyl succinic anhydride modified starch

Abstract: The purpose of this study is to reveal the mechanism of preparing high quality modified starch by ultrasonic technology. In this paper, ultrasonic modified starch and octenyl succinic anhydride modified starch with low degree of substitution were prepared under ultrasonic conditions, using sweet potato starch as raw material. The effects of ultrasound on the structure and properties of native sweet potato starch were studied to see whether ultrasound could produce mechanochemical effect on starch. Then the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Figure 2 shows the infrared spectra of the compound powder with various amounts of inulin or β‐glucan. The shape and position of the infrared absorption peaks of the systems with inulin or β‐glucan were largely similar to those of CK1 and CK2; no new absorption peaks appeared, indicating that no new groups reflecting the association between inulin or β‐glucan with potato flour through hydrogen bonds were generated(Zhang et al, 2020). A broad absorption peak in the range of 3700–3200 cm −1 represented stretching vibration of the hydroxyl groups shared between polymers.…”
Section: Results and Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…Figure 2 shows the infrared spectra of the compound powder with various amounts of inulin or β‐glucan. The shape and position of the infrared absorption peaks of the systems with inulin or β‐glucan were largely similar to those of CK1 and CK2; no new absorption peaks appeared, indicating that no new groups reflecting the association between inulin or β‐glucan with potato flour through hydrogen bonds were generated(Zhang et al, 2020). A broad absorption peak in the range of 3700–3200 cm −1 represented stretching vibration of the hydroxyl groups shared between polymers.…”
Section: Results and Analysismentioning
confidence: 91%
“…Compared with CK2, the peak position of the compound flour with polysaccharide shifted into the range of 3700–3200 cm −1 , probably because the polysaccharide contained a large number of hydroxyl groups and O–H stretching vibration were enhanced after mixing with potato flour. In addition, there was a sharper peak near 2926 cm −1 due to the C–H2 stretching vibration (Zhang et al, 2020), as well as absorption peaks between 1250 and 900 cm −1 corresponding to the C–O and C–N stretching vibrations (Li, Cui, et al, 2021). However, the structure did not differ according to the type or addition amount of polysaccharide, and the reasons need further study.…”
Section: Results and Analysismentioning
confidence: 99%
“…9 For instance, a study by Zhang et al showed that ultrasound-modified potato starch could effectively enhance the oral absorption of poorly water-soluble drugs, such as fenofibrate, by improving their solubility and dissolution rate. 39 Applications of starch modified by ultrasound techniques have been shown in Figure 3.…”
Section: Improved Bioavailabilitymentioning
confidence: 99%
“…Due to their unique physicochemical properties, ultrasound-modified starches are becoming increasingly important in drug delivery. 39 However, concerns have been raised regarding the stability and biocompatibility of these modified starches. In terms of physicochemical stability, studies have shown that ultrasound modification can result in changes to the molecular weight, particle size, and surface charge of starches.…”
Section: Stability and Biocompatibility Of Ultrasound-modified Starchesmentioning
confidence: 99%
See 1 more Smart Citation